Trends in obesity, overweight, and malnutrition among children and adolescents in Shenyang, China in 2010 and 2014: a multiple cross-sectional study - Lingling Zhai; Youdan Dong; Yinglong Bai; Wei Wei; Lihong Jia (BMC, 2017)
Abstract Background The prevalence, characteristics, and trends in obesity, overweight, and malnutrition among children and adolescents in 2010 and 2014 in Shenyang, China was described. Methods This was a multiple cross-sectional study using data from the 2010 and 2014 National Survey on Students' Constitution and Health. A total of 31,031 children and adolescents were included in this survey. Differences in the percentages of obesity, overweight, and malnutrition by age, gender, and living region in 2010 and 2014 were compared using the χ2 test. Stepwise logistic regression was performed to select potential covariates for the dependent variable (overweight, obesity, or malnutrition). Results The prevalence of obesity and overweight in 2010 was 8.99% and 13.72%, respectively, and 12.64% and 14.06% in 2014, respectively. The prevalence of malnutrition was 10.68% and 10.69% in 2010, and 2014, respectively. In 2010 and 2014, boys and girls 7-11 years of age had higher rates of obesity than other age groups (P < 0.01). The prevalence of obesity and overweight was significantly higher in the urban residents compared to the rural residents, and was also significantly higher in boys than girls (P < 0.01); however, the prevalence of malnutrition was significantly lower in boys than girls (P < 0.01). Compared to 2010, the prevalence of obesity in 2014 increased significantly in boys and girls, and urban and rural residents (P < 0.05), but the prevalence of malnutrition did not change. The prevalence of obesity, overweight, and malnutrition was associated with gender, age, and living region by univariate logistic regressions. Conclusion The prevalence of obesity and overweight has continuously risen since 2010, and there is a low-age trend of obesity and overweight among children and adolescents in Shenyang, China. The increasing rate of obesity and overweight was faster in rural than urban areas. Malnutrition did not significantly decrease during the 4-year period from 2010-2014.